One-pot hydrothermal synthesis of molybdenum nickel sulfide with graphene quantum dots as a novel conductive additive for enhanced supercapacitive performance. Issue 8 (16th October 2020) - Sangabathula, Omkar; Sharma, Chandra S.
Abstract : 3D flower-like GQD induced metal doped nickel sulfide was grown on Ni-foam. The MNS-G-2.5 composite delivered a superior specific capacitance and an impressive cyclic stability. In addition, the MNS-G-2.5//rGO ASC has an exceptional energy density. Abstract : We depict a facile as well as an economical one-step hydrothermal method, for the first time, to synthesize a hierarchical three-dimensional (3D) flower-like structure of molybdenum (Mo) particle decorated nickel sulfide and its composite with graphene quantum dots (GQDs) for high-performance supercapacitor applications. An optimum coupling of GQDs with Mo doped nickel sulfide (MNS-G) enhances the electrical conductivity further by creating more active sites and thus helps in modulating the electrochemical behavior of the composite. The prepared MNS-G-2.5 composite (2.5 wt% GQD) exhibits a superior specific capacitance of 2622 F g −1 at 1 A g −1 and shows an excellent coulombic efficiency of 92.2% after 10 000 cycles at a current density as high as 20 A g −1 . The fabricated aqueous-based asymmetric supercapacitor device exhibits an excellent energy density of 38.9 W h kg −1 at a power density of 416.6 W kg −1 with an impressive capacitance retention and coulombic efficiency of 96.4% and 95.9%, respectively, after 10 000 charge–discharge cycles. These outstanding electrochemical properties of GQD- and molybdenum-incorporated nickel sulfide pave the way for the development of efficient electrode materials for practical supercapacitor applications.